Cover Image: Volume 20, Issue 2. Issue 2 (1st March 2018) - Rice, Gavin; Barmina, Olga; Hu, Kevin; Kopp, Artyom
Abstract : The cover image, by Gavin Rice et al., is based on the Research Evolving doublesex expression correlates with the origin and diversification of male sexual ornaments in the Drosophila immigrans species group, DOI10.1111/ede.12249 .